1988
DOI: 10.1111/j.1365-2125.1988.tb03383.x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed‐release mesalazine (5‐aminosalicylic acid): coat dissolution and excretion in ileostomy subjects.

Abstract: Medicine and Dentistry, London and 2Leigh Infirmary, Leigh 1 Delayed-release mesalazine has been formulated to deliver 5-aminosalicylic acid to the colon. We have therefore studied the ileostomy excretion and coat dissolution of this preparation. 2 Following ingestion of a single tablet 88% (range 69-114%) of the 400 mg dose appeared unchanged in the ileosomy effluent over the subsequent 12 h. 3 Ileostomy effluent pH appeared to be a major determinant of 5-aminosalicylic acid release. 4 In vitro studies revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 15 publications
(13 reference statements)
0
15
0
Order By: Relevance
“…Direct evidence on pH dependent release in ulcerative colitis is not yet available but preliminary data suggest that in most patients small bowel pH, measured with a radiotelemetry capsule,12 is high enough for sufficient time to allow capsule dissolution 47. In vitro studies have shown that a low pH inhibits colonic bacterial metabolism of carbohydrate, urea, and other nitrogenous compounds21: it is possible that increased colonic acidity could also reduce azo reductase activity and release of 5-ASA from sulphasalazine, olsalazine, and balsalazide 49a…”
Section: Potential Effects Of Altered Colonic Ph and Transit On Bioavmentioning
confidence: 99%
“…Direct evidence on pH dependent release in ulcerative colitis is not yet available but preliminary data suggest that in most patients small bowel pH, measured with a radiotelemetry capsule,12 is high enough for sufficient time to allow capsule dissolution 47. In vitro studies have shown that a low pH inhibits colonic bacterial metabolism of carbohydrate, urea, and other nitrogenous compounds21: it is possible that increased colonic acidity could also reduce azo reductase activity and release of 5-ASA from sulphasalazine, olsalazine, and balsalazide 49a…”
Section: Potential Effects Of Altered Colonic Ph and Transit On Bioavmentioning
confidence: 99%
“…SASP has, further, been shown to have a unique place in prophylactic treatment of inactive UC in contrast to corticosteroids (77). Thus, 2 g SASP for one year reduced clinical relapse significantly from 24/33 in the placebo-group to 6/ 34 in the SASP group, with the reservation that compliance was not perfect in the treated group (97). Later, placebo-controlled longterm-studies found the efficacy rates of SASP to be a reduction of relapse from 55% in the placebo group to 12% (35).…”
Section: Sasp Treatment In Ulcerative Colitismentioning
confidence: 99%
“…From the comparison of intestinal elimination of SASP and 5-ASA sustained-release formulations by Bondesen et al (111) and other observations (73,97), it is concluded that systemic kinetics alone are erroneous in predicting the regional availability from a SR-drug. Although, the systemic kinetics of SR-drugs imply low availability, regional intestinal concentrations of 5-ASA may be sufficient for local drug-effect (111).…”
Section: Vi424 Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Various modified-release peroral formulations have been developed that target the dissolution of the tablets to specific sections of the gastrointestinal tract. Acrylic polymer coated tablets (Claversalg, Mesalazine®) are designed to dissolve at pH > 6 thereby making the drug topically available in the more proximal parts of the intestine (Riley et al, 1988). Normally only a small fraction of the dose is absorbed from the gastrointestinal tract.…”
mentioning
confidence: 99%